Sponsored Article: Women In STEM: Interview with Anna Rafferty - Andersen, Kristen; Janes, Ava (Trinity Student Medical Journal, 2024)
Encouraging diversity in the workplace has the potential to “change the trajectory of health for humanity” says Anna Rafferty, Director of Strategy at Johnson & Johnson Campus, Ireland. Promoting such representation, particularly in the area of STEM, has been one of the key aims of Johnson & Johnson’s WiSTEM2D undergraduate programme since its creation in 2016. As a leader of this programme, Anna started her career with Johnson & Johnson in 2003 after graduating with a BSc in Biotechnology from the National University of Ireland, Galway, and later a Graduateship in Marketing from the Technological University of Dublin. She is now a central figure in the undergraduate WiSTEM2D programme in Ireland. We spoke to Anna about the about the WiSTEM2D programme, the difficulties and challenges faced by women in STEM careers, and what she believes universities can do about it.